(untitled) (INTI Nusa Mandiri, 2023)
Abstract— Nowadays, awareness of the importance of cultural heritage is decreasing among the public, especially among youth who will become leaders and inherit the culture of their region. Law Number 11 of 2010 stipulates the importance of protecting and preserving cultural heritage because it has significant value in history, science, education, religion and culture. Therefore, the existence of cultural heritage must be considered and maintained properly according to applicable regulations. There are several criteria for assessing buildings that will be used as cultural heritage according to Law number 11 of 2010 in Chapter III, article 5, cultural heritage criteria, namely the age of the building, historical value, cultural value and architectural value. This study aims to create a system that can determine the feasibility of a building as a cultural heritage in a precise and accurate way (case study DISPORAPARBUD Purwakarta). In this study, the Simple Multi Attribute Rating Technique (SMART) method was used in the Decision Support System (SPK). The results of this study are to produce recommendations for buildings that are worthy of being cultural heritage in accordance with predetermined criteria, namely the Normal School building with a value of 1 by occupying the first rank, which will then be recommended to the Purwakarta DISPORAPARBUD